Experimental investigation of the mechanical behaviour of gravel-granulated tyre rubber mixtures. (1st March 2021) - Tasalloti, Ali; Chiaro, Gabriele; Banasiak, Laura; Palermo, Alessandro
Graphical abstract: Highlights: The mechanical behaviour of gravel-rubber mixtures is experimentally investigated. Three packing states for two-size soft/rigid binary mixtures were identified. Rubber content and size significantly influence the compressibility and strength. A framework with performance-based design criteria was proposed. Mixtures with VRC ≤ 40% are suitable structural fill materials in geo-applications. Abstract: Recycling and reuse of end-of-life tyres (ELTs) in civil engineering applications is an effective way to minimise environmental and health issues associated with such waste materials and concurrently reduce high demand of natural aggregates. In this study, direct shear tests were carried out to evaluate the strength and deformation properties of two types of gravel-granulated tyre rubber (G-GTR) mixtures under four levels of normal stress (6.5, 30, 60, and 100 kPa). Mixtures were prepared at different volumetric rubber content ( VRC) of 0%, 10%, 25%, 40% and 100%, by using a combination of small and large rubber particles mixed with a rounded uniform gravel. The results indicated that VRC and normal stress are the main parameters that influence the mechanical behaviour of G-GTR mixtures, while, the effect of rubber size is more noticeable at lower VRC . Based on the experimental findings, a framework with compressibility and strength performance-based criteria for the selection of G-GTR mixtures as structural fills for geotechnical applications is proposed. It is recommended that, as long as one-dimensional compressive strains are acceptable, mixtures with VRC ≤ 40% are suitable materials for the majority of geotechnical engineering applications, since the friction angle is generally > 30°.